Low-dose mitomycin C, etoposide, and cisplatin for invasive vulvar Paget's disease. Issue 3 (1st April 2002) - Watanabe, Y; Hoshiai, H; Ueda, H; Nakai, H; Obata, K; Noda, K
Abstract : Abstract: Watanabe Y, Hoshiai H, Ueda H, Nakai H, Obata K, Noda K. Low-dose mitomycin C, etoposide, and cisplatin for invasive Paget's disease. We report the effect of low-dose mitomycin C, etoposide, and cisplatin (low-dose MEP) therapy for three patients with invasive vulvar Paget's disease (invasive VPD) who declined radical vulvectomy and skin grafting. One patient achieved a complete response, while the other two showed partial responses (PR) without grade 3 or 4 adverse effects. The two patients with PR were undergone partial vulvectomy and inguinal lymph node dissection. All patients have no sign of recurrence for 10 months after chemotherapy. Our present results suggest that low-dose MEP is an effective and safe chemotherapy for invasive VPD and low-dose MEP may significantly improve postoperative quality of life in patients with invasive VPD by avoiding extensive vulvar resection and skin grafting.